CONCEPT OF LEAN PRODUCTION AS THE BASIS OF SUSTAINABLE BUSINESS - Karpenko, Yuliia (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The abstract of the report examines the modern concept of lean production, in particular the possibilities of using its tools (methods and techniques) to achieve the goals of sustainable development of the enterprise. The possible effect of using the tools of the concept of lean production in the context of sustainable development is described.